Keanekaragaman Jamur Makroskopis di Kawasan Hutan Universitas Palangka Raya Kalimantan Tengah - Desimaria Panjaitan; Vinsen Willi Wardhana; Santi Dwi Febiolasari (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2022)
Macroscopic fungi comprise a very diverse group of heterotrophic and mostly saprophytic organisms. This research purpose was to identify the diversity of macroscopic fungi from the forest of University of Palangka Raya. The fungi samples were collected from May until June 2021 using purposive sampling method. The samples were identified based on macroscopic characters such as the form of fruiting bodies, lamellae, cap shape and colours. There were 18 species of Basidiomycota which consist of 9 famili and 12 genera. The species were identified as Agrocybe sp., Auricularia sp.1, Auricularia sp.2, Collybia sp., Dacryopinax spathularia, Ganoderma sp.1, Ganoderma sp.2, Ganoderma sp.3, Hygrocybe sp., Marasmiellus sp., Mycena sp.1, Mycena sp.2, Pycnoporus sanguineus, Schizophyllum commune, Trametes sp.1, Trametes sp.2, Trametes sp.3, and Tyromyces sp. Descriptions of each species were provided.